Exploring Student Motivation in Arabic Language Learning at State Madrasah Aliyah Schools in Samarinda - Molyono, Edy Rizki; Syuhadak, Syuhadak; Ifawati, Nur Illa; Raihan, Muhammad Luthfi Ridho (Borneo Journal of Language and Education, 2026)
Low student motivation remains one of the most persistent barriers to successful foreign language acquisition, particularly in Arabic language learning at madrasahs, where variations in teaching strategies often fail to fully engage learners. This study aims to analyze students' motivation in Arabic language learning and its role in promoting academic achievement at State Madrasah Aliyah 1 Samarinda and State Madrasah Aliyah 2 Samarinda. This research employed a descriptive qualitative approach with a multi-case study design. Data were collected through observation, interviews, and documentation involving Arabic language teachers of grades X–XII and selected high-achieving students. Data were analyzed using the Miles, Huberman, and Saldana interactive model, including data condensation, data display, and conclusion drawing. The findings reveal that both madrasahs implement the Merdeka Curriculum with distinct instructional characteristics: MAN 1 emphasizes game-based, engaging learning, while MAN 2 focuses on academically challenging instruction. Students' motivation is shaped by intrinsic and extrinsic factors, which in turn influence their competencies in vocabulary, speaking, grammar, and reading. Strengthening both motivation and instructional strategies is essential to improve learning outcomes.